El tiempo vuela: Metáforas cognitivas y fraseologismos con dominio meta TIEMPO en español y alemán (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
Within the framework of Cognitive Linguistics, this paper aims to carry out an analysis of a series of phraseologisms in Spanish and German, extracted from different dictionaries, which have ‘time’ as their target domain. The objective is to show which cognitive metaphors are most recurrent in both languages within this conceptual domain, paying special attention to the metaphor TIME IS SPACE in its various facets, e.g., in relation to the passage of time. According to Lakoff/ Johnson’s taxonomy (1980), many of the cognitive metaphors studied are based on the image schemas PATH and can be classified as ontological and/or orientational metaphors. Finally, I will present some metaphors in which the cultural component predominates, such as TIME IS A LIMITED RESOURCE or TIME IS A REVEALER OF TRUTH, which can be found in both languages.
Keywords: cognitive metaphor, target domain ‘time’, contrastive Spanish-German Phraseology, Cognitive Linguistics